Z zagadnień recepcji młodopolskiej liryki symbolicznej przez uczniów szkoły średniej = On the Reception of Young-Polish Symbolical Lyric Poetry by Secondary School-Pupils - Ogłoza, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article tries to describe partially at least the reading of young-Polish symbolical lyrists by Secondary School pupils. In the first part of this article and on the grounds of different documents or reception the motives for the pupils'interest in lyric poetry of that period are characterized and their estimation of the read texts is given. The second part of this article shows the reason for false or insufficient interpretation of symbolical lyric poetry by the pupils, resulting from insignificant competence in the analysis of the literary text and of too little knowledge in the sphere of interpretation of the lyrists in vernacular context.
Keywords: liryka; symbolizm; literatura polska - 20 w.; nauczanie